Encapsulation of winged termites in cellulose nanofibre for the fabrication of cellulose bioplastic / Syahidatul Nadhilah Shah Lail ... [et al.] - Shah Lail, Syahidatul Nadhilah; Aizul Hussin, Noorul Jannah; Kaco, Hatika; Sajab, Mohd Shaiful (2021)
Currently, bioplastic has become a trend due to the undegraded petroleum-based plastic, hence leading to environmental pollution. Meanwhile, the winged termite swarmers come out when the environment is wet or damp, so they are often found after rain. Meanwhile, cellulose is the most abundant biopolymer on Earth. It is highly valuable, renewable, biodegradable, bio-compatible, and most importantly, not fully utilised. Hence, the aims of this study were to integrate winged termites and cellulose in the production of bioplastic and study the thermal and chemical properties of the bioplastic produced which will become an alternative to save the environment. Cellulose was dissolved in pre-cooled LiOH/urea solvent at -13°C to form a cellulose solution. Termite wings were then grinded using pestle and mortar. The termite wings powder was added and mixed with cellulose solution until it was fully dissolved. The termite wings powder-infused cellulose solution was cast on a glass plate and flattened out and consequently was coagulated in acid bath to form a cellulose membrane. The sample was then frozen and air-dried. From the FTIR analysis, the functional group of termites and cellulose were changed after the regeneration of cellulose and mixing with termites has been carried out. This portrayed that the reaction has taken place. The thermal properties of the bioplastic were investigated using DSC and revealed that winged termites have enhanced the thermal properties of the plastic. Consequently, this bioplastic also serves as green plastic which helps to reduce pollution by making bioplastics using the waste from natural source.